2003
DOI: 10.1080/01411920301852
|View full text |Cite
|
Sign up to set email alerts
|

Is Mathematics T.I.R.E.D? A Profile of Quiet Disaffection in the Secondary Mathematics Classroom

Abstract: Research often focuses on disaffection in the mathematics classroom as evident in disruptive behaviour, absenteeism or special needs: thus, it ignores a group of students whose disaffection is expressed in a tacit, non-disruptive manner, namely as disengagement and invisibility. Ignoring this often large group implies that the mathematical potential of these learners may remain defunct. This article reports on a one-year study of quiet disaffection conducted in three Year 9 mathematics classrooms in Norfolk. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 34 publications
9
91
0
1
Order By: Relevance
“…Osborne et al (1997), in a comprehensive research review of participation in STEM subjects, reported that the main reasons why students chose to discontinue their study of mathematics were that it is perceived to be 'hard ', 'boring' and 'useless'. This is consistent with findings from more recent studies about attitudes (e.g., Nardi and Steward 2003;Kyriacou and Goulding 2006). Osborne et al also highlighted the case of girls, whose participation was and continues to be significantly lower than that of boys, in spite of similar attainment at age 16.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Osborne et al (1997), in a comprehensive research review of participation in STEM subjects, reported that the main reasons why students chose to discontinue their study of mathematics were that it is perceived to be 'hard ', 'boring' and 'useless'. This is consistent with findings from more recent studies about attitudes (e.g., Nardi and Steward 2003;Kyriacou and Goulding 2006). Osborne et al also highlighted the case of girls, whose participation was and continues to be significantly lower than that of boys, in spite of similar attainment at age 16.…”
supporting
confidence: 93%
“…While they resonate with Nardi and Steward's (2003) findings of numb disinterest and disengagement from mathematics, our written responses were often charged with emotion:…”
Section: Maths Is Boring I Don't Enjoy Itsupporting
confidence: 65%
See 2 more Smart Citations
“…Usual school mathematics refers to the pervasive form in which mathematics has been and continues to be taught in schools in the UK (Boaler, 1997a(Boaler, ,1999(Boaler, , 2000Boaler & Greeno, 2002;Boaler, Wiliam & Zevenbergen, 2000;Boylan, 2004;Cotton, 1998;Ernest, 1998;Mendick, 2006;Nardi & Steward, 2003) and, in spite of the recent reform movement, in the US (Anderson, 1997;Cobb, Wood, Yackel, & McNeal, 1992;Gregg, 1995;Stigler & Hiebert, 1997). Many aspects of usual school mathematics are common features of the way mathematics is taught in schools elsewhere.…”
Section: The Students Are Given Tests Regularly (Generally Every Halmentioning
confidence: 99%